2020
DOI: 10.1002/mus.26823
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of body composition as a potential biomarker in spinal muscular atrophy

Abstract: Introduction We aimed to investigate the correlation between body composition (BC) and spinal muscular atrophy (SMA)‐specific motor function assessments. Methods Patients with SMA types I or II, aged 1 to 10 years, were recruited in this cross‐sectional study. The protocol included anthropometric measurements, and dual‐energy X‐ray absoprtiometry to assess fat mass (FM), lean mass (LM), fat‐free mass (FFM), FM and FFM indexes (FMI, FFMI), and motor function assessments (Children's Hospital of Philadelphia Infa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 17 publications
(31 reference statements)
2
11
0
1
Order By: Relevance
“…Some patients with acceptable fat mass (FM) may plot as underweight since the BMI underestimates their body fat [ 50 , 51 , 57 ]. Relative to age and sex, these patients have a higher fat mass index (FMI) and lower lean tissue, which puts them at a higher risk of overweight status when compared to healthy children [ 46 , 54 , 57 , 58 , 59 ]. Across SMA groups, fat-free mass (FFM) and lean body mass (LBM) distribution are also different.…”
Section: Baseline Anthropometric Data and Energy Expenditure Of Sma Patientsmentioning
confidence: 99%
“…Some patients with acceptable fat mass (FM) may plot as underweight since the BMI underestimates their body fat [ 50 , 51 , 57 ]. Relative to age and sex, these patients have a higher fat mass index (FMI) and lower lean tissue, which puts them at a higher risk of overweight status when compared to healthy children [ 46 , 54 , 57 , 58 , 59 ]. Across SMA groups, fat-free mass (FFM) and lean body mass (LBM) distribution are also different.…”
Section: Baseline Anthropometric Data and Energy Expenditure Of Sma Patientsmentioning
confidence: 99%
“…Because we do not have nontreated controls, the increase in BMI centiles in patients with SMA2 could also be due to the natural course of SMA itself like reported in previous studies that identified a high proportion of overweight in patients with SMA2. 2,12 Due to the high prevalence of increased fat mass in SMA 6,8,14 and the missing data of body composition, further studies need to analyze the effect of nusinersen on body composition including fat and muscle mass. Further, we did not evaluate confounding factors such as nutritional supplementation, high-caloric diet, and dysphagia in our study, which could lead to weight loss/gain in effected individuals.…”
Section: Discussionmentioning
confidence: 99%
“…A total body image was obtained, with computer‐generated estimates for the percentage of total body fat, LBM, and bone. Similar to a recent study of body composition in SMA patients, fat‐free mass was calculated as the sum of lean mass and bone mineral content divided by total body mass and expressed as a percentage 31 . Whole‐body oxygen consumption (VO 2 ) relative to LBM was also calculated as absolute VO 2 at peak exercise (mL/min) divided by LBM (kg) from DEXA.…”
Section: Methodsmentioning
confidence: 99%